2019
DOI: 10.1016/j.jiac.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide study of outpatient oral antimicrobial utilization patterns for children in Japan (2013–2016)

Abstract: Background: Antimicrobial resistance (AMR) is a major multinational public health concern. The Japanese government set goals in its AMR action plan to reduce use of oral cephalosporins, macrolides, and quinolones by half between 2013 and 2020. We aimed to evaluate antimicrobial use in children in Japan by observing prescription patterns as an interim assessment of the national AMR action plan. Methods: Using the national health claims database, we retrospectively analyzed all oral antimicrobials dispensed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The use of antibiotics in children peaks at the age of one year in Japan [10]. In other countries antibiotics also tend to be prescribed more frequently in younger children Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibiotics in children peaks at the age of one year in Japan [10]. In other countries antibiotics also tend to be prescribed more frequently in younger children Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of oral antibiotics is reportedly higher in children (< 15 years) and the elderly (≥65 years) than in individuals aged 15-64 years [9]. Additionally, the highest prescription rates of all antimicrobials is among children aged 1-5 years, peaking at age 1 year [10]. Efforts to improve antibiotic prescribing practices need to incorporate some complementary strategies: changing physicians' behavior [11], patient education, and modifying the healthcare system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese antimicrobial consumption surveillance reported that oral antimicrobials accounted for 92.6% of total consumption and oral third-generation cephalosporins accounted for 23.8% of all oral antimicrobials in 2013 [15]. Another Japanese nationwide study of outpatient oral antimicrobial utilization patterns for children reported that oral third-generation cephalosporins accounted for 35.6% of all antimicrobials dispensed in 2013 to 2016 [37]. Unlike in European countries or the United States, the consumption of oral third-generation cephalosporins has been particularly high in Japan [15][16][17], although those were suggested to increase AMR [19,21,25], cause hypocarnitinemia particularly in children [29 -31], and be an important risk factor for CDI [32].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Josephine et al carried out a detailed analysis on the variability of prescriptions in certain hospitals (considering a population of children without comorbidities who had received antibiotics) by country, focus of the infection (particularly with respect to the respiratory tract) and type of antibiotic; they noted that differences in patient combination, diagnostic evaluation or hospital characteristics could not justify all the variability of antibiotic prescription, thus suggesting overuse ( van de Maat et al, 2019). Interestingly, using the national health claims database, Kinoshita et al retrospectively analyzed all oral antimicrobials dispensed from outpatient pharmacies in Japan to children under 15 years old from 2013 to 2016 by age, prefecture, type of antimicrobial, and year (Kinoshita et al, 2019). They showed that antimicrobials administered to pediatric patients in Japan did not decrease.…”
Section: Overview On Antibiotic Resistancementioning
confidence: 99%